Cytokine profiling in plasma distinguishes the histological inflammatory subtype of head and neck squamous cell carcinoma and a novel regulatory role of osteopontin - Ghita, Ioana; Piperi, Evangelia; Atamas, Sergei P.; Bentzen, Soren M.; Ord, Robert A.; Dyalram, Donita; Lubek, Joshua E.; Younis, Rania H. (Frontiers in Oral Health, 2022)
Head and neck squamous cell carcinoma (HNSCC) can be classified according to the histological inflammatory subtype (HIS) into inflamed (HIS-INF), and or immune excluded (HIS-IE). The HIS-IE was previously associated with higher levels of soluble Semaphorin4D (HsS4D) in plasma and higher transcriptional levels of Osteopontin (OPN) in the tumor tissue, compared to the HIS-INF. The goal of the current study is to investigate if the HIS inflammatory subtype can be distinguished by a differential cytokine panel in peripheral blood. Retrospectively collected, five HIS-INF and five HIS-IE tumor tissue with paired plasma were included in the study. Five healthy donors (HD) and five autoimmune/chronic inflammatory conditions (AI/CI) were controls. ELISA-Luminex™ System was used to detect 40 traditional cytokines in plasma. Human cytokine array (104 cytokines) was used for the conditioned medium (CM) of the HNSCC HN6 cell line . Semaphorin4D (Sema4D) siRNA, and recombinant human Osteopontin (rh-OPN) were used to investigate the effect of OPN on Sema4D expression. The HIS-IE cytokine profile was higher than the HIS-INF but comparable to the AI/CI. The HIS-INF had the lowest cytokine levels. The HIS-IE was differentially higher in IP-10 and IL8 compared to HD, while the HIS-INF was higher in IL-10. Sema4D inhibition in HN6 resulted in decrease of OPN in the CM of HN6, and treatment with rh-OPN rescued Sema4D in HN6 cell lysate and associated CM. In conclusion, the current work demonstrates a novel association between the HIS subtype and differential pattern of cytokines expression in plasma. These findings can open new avenues for HNSCC patient stratification and hence better personalized treatment.